2016
DOI: 10.1007/s11661-016-3470-2
|View full text |Cite
|
Sign up to set email alerts
|

Powder Bed Layer Characteristics: The Overseen First-Order Process Input

Abstract: Powder Bed Additive Manufacturing offers unique advantages in terms of manufacturing cost, lot size and product complexity compared to traditional processes such as casting, where a minimum lot size is mandatory to achieve economic competitiveness. Many studies -both experimental and numerical -are dedicated to the analysis of how process parameters such as heat source power, scan speed and scan strategy affect the final material properties. Apart from the general urge to increase the build rate using thicker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 20 publications
6
68
0
Order By: Relevance
“…This is in agreement with observation made for other powders [7]. Figure 4 shows the particle size distribution obtained for two different table displacements, 35 and 50 µm, and compares them the input powder size distribution.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This is in agreement with observation made for other powders [7]. Figure 4 shows the particle size distribution obtained for two different table displacements, 35 and 50 µm, and compares them the input powder size distribution.…”
Section: Resultssupporting
confidence: 89%
“…When modelling the powder spreading process, we use discrete element methods (DEM) to study powder spreading and the distribution of powder on the processing table [7]. DEM is a Lagrangian approach where the modelled region considers the particles inside their own point of reference describing Newton's laws of motion for conservation of momentum.…”
Section: Computational Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coating arm is assumed to be a rigid body the velocity of which is described as a boundary condition. Once the particles are created, the coating arm is set into motion spreading the particles onto the processing table [35]. Figure 5 shows the evolution of the calculated powder packing density for multiple layers.…”
Section: Power Bed Micromodelingmentioning
confidence: 99%
“…Using a discrete element model to obtain the powder bed characteristics, Mindt et al showed how the balance between powder size distribution and the slit height can affect the coating quality and powder recyclability. 9,10 The numerically obtained powder bed was transferred to the melting models to solve Navier-Stokes equations as described in Ref. 6.…”
Section: Numerical Modelsmentioning
confidence: 99%